Elementary Teachers’ Perception Toward Digital Literacy in Language Learning and Teaching - Rofi’ah; Ni Luh Putu Sri Adnyani; Putu Suarcaya (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The development of digital technology in the 21st century requires the world of education to adapt quickly, especially in language learning in elementary schools. Digital literacy is an essential competency for teachers to be able to create relevant, interesting, and meaningful learning for students. This study aims to describe elementary school teachers' perceptions of the use of digital teaching materials in language learning and analyze the role of these perceptions in encouraging classroom learning activities. This study used a descriptive qualitative approach. Data were collected through a Likert-scale questionnaire distributed to 35 elementary school English teachers in Bondowoso Regency, an in-depth interview with one teacher, and observations of the learning process. Data analysis was conducted using descriptive qualitative methods by calculating percentages. The results showed that the majority of teachers had very positive perceptions of the use of digital teaching materials, indicated by a high percentage of understanding, readiness, and confidence in the effectiveness of digital media in increasing student motivation, engagement, and understanding. However, technical obstacles were still encountered related to operational skills and device preparation time. This study concluded that positive teacher perceptions contributed significantly to the creation of more interactive and effective language learning and emphasized the importance of ongoing digital literacy training for teachers as an implication for developing elementary education in the digital era.